Correlation of hydrogen-bonding propensity and anticancer profile of tetrazole-tethered combretastatin analogues - Jedhe, Ganesh S.; Paul, Debasish; Gonnade, Rajesh G.; Santra, Manas K.; Hamel, Ernest; Tam Luong Nguyen; Sanjayan, Gangadhar J. (Bioorganic & Medicinal Chemistry Letters, 2013)
A series of 1,5-disubstituted tetrazole-tethered combretastatin analogues with extended hydrogen-bond donors at the ortho-positions of the aryl A and B rings were developed and evaluated for their antitubulin and antiproliferative activity. We wanted to test whether intramolecular hydrogen-bonding used as a conformational locking element in these analogues would improve their activity. The correlation of crystal structures with the antitubulin and antiproliferative profiles of the modified analogues suggested that hydrogen-bond-mediated conformational control of the A ring is deleterious to the bioactivity. In contrast, although there was no clear evidence that intramolecular hydrogen bonding to the B ring enhanced activity, we found that increased substitution on the B ring had a positive effect on antitubulin and antiproliferative activity. Among the various analogues synthesized, compounds 5d and 5e, having hydrogen-bonding donor groups at the ortho and meta-positions on the 4-methoxy phenyl B ring, are strong inhibitors of tubulin polymerization and antiproliferative agents having IC50 value in micromolar concentrations. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Colchicine; Combretastatin; Crystal; Tetrazole; Tubulin

Synthesis and anticancer activity of conformationally constrained Smac mimetics containing pseudo beta turns - Baravkar, Sachin B.; Wagh, Mahendra A.; Paul, Debasish; Santra, Manas; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2018)
Herein, we report synthesis and in vitro anticancer activity of conformationally constrained Smac mimetics containing reverse turn inducing motifs "Ant-Pro" and "sAnt-Pro". The synthesis of Smac analogs with diverse hydrophobic groups at the C-terminus was carried out using solution phase peptide synthesis. The synthesis of Ant-Pro containing analogs 3a-j was carried out by ring opening of benzoxazinones 7a-c, whereas, their sulfonamide counterparts 4a-h were synthesized by using routine acid-amine coupling reaction. In vitro anticancer studies against breast cancer cell line MDA-MB-231 revealed that some of the new analogs had better anticancer activity than the standard AVPI Smac tetrapeptide. (C) 2018 Published by Elsevier Ltd.